Internal financial determinants of stock prices in the banking sector: Comparative evidence from Dubai and Abu Dhabi Stock markets; Determinantes financieros internos de los precios de las acciones en el sector bancario: Evidencia comparativa de los mercados bursátiles de Dubai y Abu Dhabi - Chadi Azmeh; Rasha Hamada (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
The present study has been conducted to examine the impact of seven of most important internal factors on stock prices for all listed banks in Dubai and Abu Dhabi stock markets. Pooled Least Square, Fixed Effects (FE), and Random Effects (RE) models have been used to carry out the analysis for data pertaining to 23 banks for a time period between 2014-2017. The aim of the study is to examine the most important internal factors affecting stock prices in the banking sector of United Arab Emirates, and whether internal factors determining stock prices in this sector are the same for Dubai and Abu Dhabi stock markets. The results give evidence of positive and significant impact of Earnings Per Share (EPS) and Dividend Per Share (DPS) on market price for shares, in all markets for the former and only in Abu Dhabi stock market for the later. By contrast, the study reveals a negative impact of Return on Equity (RoE), Dividend Yield (DY), and Price Earnings (P_E) on market price for shares. Even more important, the study gives evidence of differentiated impact of variables representing dividend policies, on market price for shares, between the two markets investigated in United Arab Emirates.
Keywords: D53; E44; G10; 330; stock price; internal determinants; fixed and random effects; Dubai and Abu Dhabi stock markets; banking sector